Subcellular chemical imaging of structurally similar acridine drugs by near-field laser desorption/laser postionization mass spectrometry - Cheng, Xiaoling; Yin, Zhibin; Rong, Liu; Hang, Wei (Nano research, 2020)
Insights into the pharmacologic effect on cellular processes and the potential toxicological effects are vital to new drug development and evaluation, yet research on these subjects remains a great challenge due to the lack of information regarding the spatiotemporal distribution of drugs and metabolites within a single cell. Mass spectrometry imaging (MSI) has proven to be a label-free and high-throughput approach for visualizing drug distribution in spatial and temporal domains. However, single-cell drug imaging has been limited so far by detection sensitivity and microscale lateral resolution. Herein, we report near-field laser desorption/laser postionization mass spectrometry (NDPI-MS) for single-cell imaging of two structurally similar drugs, proflavine and ethacridine, and subcellular distributions of proflavine at different drug concentrations were investigated. The NDPI-MS imaging results indicate that proflavine was accumulated in lysosomes, which was verified by laser scanning confocal microscopy (LSCM). Additionally, a distinguished subcellular distribution pattern of ethacridine from proflavine could be visualized, highlighting the complexity of the interaction between the drugs and biological environment even though these two drugs possess similar structures. Taken together, the present results demonstrate the great potential of the integrated single-cell MSI platform for characterizing the drug distribution and its phenotype changes within individual cells, expediting the identification and evaluation of newly developed drugs.